Dietary Protein Affects the Growth Response and Tissue Composition of Juvenile Slipper Lobster (Thenus australiensis) - Andrea Williamson; Chris G. Carter; M. Basseer Codabaccus; Quinn P. Fitzgibbon; Gregory G. Smith (Animals, 2024)
The effect of different dietary protein levels on apparent feed intake, apparent digestibility, body composition, nutrient retention, and growth efficiency of juvenile slipper lobster (Thenus australiensis) were evaluated for 74 days. Three isoenergetic and isolipidic feeds were formulated with crude protein levels of 445, 490, and 551 g kg−1 DM, designated as P45, P50, and P55, respectively. Lobsters were fed one of these feeds in quadruplicate tanks, with eight lobsters (mean initial wet weight 6.1 ± 0.3 g) per tank in a recirculating seawater system at 27 °C. Increasing dietary protein levels significantly increased apparent feed intake, final dry weight, and daily weight gain. Dietary protein affected whole-body protein, lipid, and energy content. Lobsters fed P55 had significantly higher lipid and energy content than those fed P50 and P45. Protein content was significantly higher in lobsters fed P55 than P50, while P45 was not significantly different from either P50 or P55. Slipper lobsters grew best on a feed containing 550 g kg−1 crude protein (equivalent to 518 g kg−1 digestible protein), providing initial insights into their protein dietary requirement. This study established a foundation for developing standardized feeds, with further research needed to optimize growth performance and nutrient utilization.